Optimalisasi Rekapitulasi Faktur Pajak untuk Efisiensi Pelaporan Pajak Pertambahan Nilai - Pramesthi Sekar Maheswari; Fitriani, Nurul (Asosiasi Ahli Administrasi Indonesia, 2025)
This study aims to explore the optimization of input and output tax recapitulation through electronic invoices to improve the efficiency of Value Added Tax (VAT) reporting at PT X. The research employs a descriptive qualitative approach to analyze the effectiveness of the company’s tax recapitulation process. Data were collected through semi-structured interviews with tax consultants and direct observation of the VAT reporting process at PT X, a building materials distribution company in Sidoarjo that collaborates with Enny Consulting Tax Firm. The results show that the implementation of electronic invoices enhances the efficiency of VAT reporting, although the achieved efficiency level is still limited to around 50% due to issues such as human error, limited human resources, and data discrepancies. The findings highlight the importance of staff training, synergy between accounting and taxation functions, and the use of software such as Accurate and Excel to improve reporting accuracy. The novelty of this study lies in its in-depth analysis of the tax recapitulation process at PT X and the specific strategies proposed for optimization. Future studies are recommended to involve more companies across various industries and stakeholders, including tax office officials and e-invoice system developers, to obtain a more comprehensive perspective on the challenges and solutions in optimizing VAT reporting.